Porcine dermal matrix in the treatment of dehiscence‐type defects – an experimental split‐mouth animal trial. Issue 7 (19th February 2014) - Fickl, Stefan; Nannmark, Ulf; Schlagenhauf, Ulrich; Hürzeler, Markus B.; Kebschull, Moritz
Abstract Objectives To describe histometrical outcomes (tissue thickness, tissue height) of a porcine dermal matrix (PDX) and subepithelial connective tissue (CTG) in the treatment of dehiscence‐type defects. Material and methods In five beagle dogs buccal dehiscence defects were created on both upper canines. The defects were covered in a split‐mouth design either with a porcine dermal matrix or subepithelial connective tissue. After 4 months histometrical outcomes were evaluated using a nonparametric Brunner–Langer model. Results Neither in the test nor in the control specimen signs of inflammation or foreign body reaction was detected. Histometrically, no significant difference was found for tissue thickness and height between both treatment groups. Conclusions Porcine dermal matrix can be used for grafting of dehiscence‐type defects. Augmentation of tissue thickness seems to be comparable to subepithelial connective tissue.